2002
DOI: 10.2105/ajph.92.5.834
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Disability in Adulthood: A 20-Year Panel Study

Abstract: Disability risk was higher for obese persons, but overweight was not consistently associated with higher disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
164
1
6

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(183 citation statements)
references
References 37 publications
12
164
1
6
Order By: Relevance
“…This finding echoes a previous study in a sample of adults of all ages and not limited by health conditions, which found that being overweight was not consistently associated with higher disability 12 . The reasons may be analogous to the "effects of life-threatening disease on behavioral change," which has been found in the link of heart attack and smoking cessation behavior 26 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This finding echoes a previous study in a sample of adults of all ages and not limited by health conditions, which found that being overweight was not consistently associated with higher disability 12 . The reasons may be analogous to the "effects of life-threatening disease on behavioral change," which has been found in the link of heart attack and smoking cessation behavior 26 .…”
Section: Discussionsupporting
confidence: 84%
“…We argue that the simultaneous measure of BMI and disability in their study may have obscured the real (or lagged) association between change in BMI and change in disability. In another study that examined the lagged effect of BMI on disability, Ferraro and colleagues 12 found that disability risk was higher for obese persons, but that overweight was not consistently associated with higher disability. Whether this pattern exists in adults living with diabetes is not yet known.…”
mentioning
confidence: 99%
“…[25][26][27] These findings indicate that BMI is indeed a causal factor at least in the upper end of the BMI spectrum. The findings by Ferraro et al 28 also support this, although they investigated self-reported disability and not disability pension. On the basis of repeated BMI measurements, they found subjects becoming obese over 10-20 years to experience increased disability.…”
Section: Bmi Status and Disability Pension M Neovius Et Almentioning
confidence: 72%
“…2 It is well known that obesity increases the risk of cardiovascular disease, several cancers, diabetes, as well as other chronic conditions. 3,4 Obesity in middle-aged and older adults has also been shown to increase the risk of physical disability, [5][6][7][8][9][10] possibly as a result of these chronic conditions or by other mechanisms. Some have suggested that the growing prevalence of obesity, particularly among younger age groups, could reverse the recent declines in disability rates among future generations of elderly as well as contribute to increasing disability rates among middle-aged and younger adults.…”
Section: Introductionmentioning
confidence: 99%
“…Some have suggested that the growing prevalence of obesity, particularly among younger age groups, could reverse the recent declines in disability rates among future generations of elderly as well as contribute to increasing disability rates among middle-aged and younger adults. 11,12 Although the association between obesity in middle and late adulthood and physical disability is well documented, [5][6][7][8][9][10] few studies have examined the impact of obesity among younger adults or the cumulative effect of obesity from young to late adulthood on physical disability later in life. [13][14][15] In the National Health and Nutrition Examination Survey, recalled weights at ages 25 and 40 were significantly correlated with self-reported physical disability in men and women aged 60-87.…”
Section: Introductionmentioning
confidence: 99%